Strategies for Communicating Climate Change to Extension Audiences - Claire Layman Bode; Martha C. Monroe; Mark A. Megalos (EDIS)
This publication is second in a series on climate change communication for Extension professionals. This 5-page fact sheet provides strategies for overcoming challenges in communicating about climate change. Written by Claire Needham Bode, Martha C. Monroe, and Mark Megalos, and published by the UF School of Forest Resources and Conservation, January 2017.